PERANCANGAN OUTER SULAM DENGAN BAHAN KAIN TENUN SESERAN KHAS TUBAN - Bayu, bayupujiubaidillah (Hastagina : Jurnal Kriya Seni, 2025)
This creative research aims to explore the visual, structural, and symbolic potential of Tenun Seseran, a traditional handwoven fabric from Kerek District, Tuban, as the primary material in contemporary outerwear fashion design. Tenun Seseran is a variant of Tenun Gedog, characterized by its loose weave, coarse texture, and natural tones such as broken white and brown. Historically, this fabric was used by coastal fishermen for straining small fish, but over time, its function and relevance have diminished in modern contexts. Therefore, this research seeks to transform the utility and cultural meaning of Tenun Seseran through a design approach that is exploratory, experimental, and reflective.The creative process began with field observation and visual documentation in the area where Tenun Seseran is produced, followed by design exploration through sketching, textile manipulation experiments, and the development of outerwear forms aligned with contemporary fashion trends. The final outcomes include six outerwear designs—consisting of cardigans, kimono-style garments, and loose-fit jackets that balance traditional aesthetics with modern forms. The works demonstrate that Tenun Seseran, despite its rough and open-weave character, holds significant potential within the discourse of eco-fashion and locally rooted design.Conceptually, this project emphasizes the transposition of tradition into modern design language without erasing the material’s cultural and textural identity. The results not only offer a fresh visual solution but also serve as a cultural articulation tool within the realm of contemporary craft design. This creative work aspires to inspire further development of textile-based crafts rooted in cultural heritage, contributing to a more sustainable and culturally conscious creative industry.